2009
DOI: 10.1002/chem.200902115
|View full text |Cite
|
Sign up to set email alerts
|

Observing Second‐Order Nonlinear Optical Properties by Symmetry Breaking in Centrosymmetric Furan‐Containing Oligoaryl Cyclophandienes

Abstract: Centrosymmetric furan-containing cyclophandienes 3 and 4, synthesized by our furan annulation protocol, have been shown to exhibit extraordinarily large Stokes shifts and second-order nonlinear optical beta values. The beta values for 3 and 4 measured at 1.32 mum are 208 and 530x10(-30) esu, respectively. The beta values of 3 and 4 are similar to those of respective cyclophenes 1 a and 7 in which strong hyperpoarizable interactions between two twisted pi-systems (oligoaryl and bridging double bond) might take … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 72 publications
0
6
0
Order By: Relevance
“…Particularly, Bazan et al have exploited the advantage of well-defined three-dimensional structures in cyclophanes that contains [2.2]paracyclophane core and found their potential applications in designing organic nonlinear optical materials [16,17]. More recently, it has been shown that chromophores with twisted π-electron systems in a cyclophane system having five-membered hetero-aromatic rings as electron donors and a bridging double bond as electron acceptor exhibit molecular hyperpolarizability with exceptionally high μβ values [18,127]. Interestingly, quantum-chemical calculations suggest that these cyclophane architectures with one or two unsaturated bridging double bonds reveal intramolecular charge transfer characteristics in the lowest excited state [18,127].…”
Section: Charge-transfer Interactions In Cyclophanesmentioning
confidence: 99%
See 2 more Smart Citations
“…Particularly, Bazan et al have exploited the advantage of well-defined three-dimensional structures in cyclophanes that contains [2.2]paracyclophane core and found their potential applications in designing organic nonlinear optical materials [16,17]. More recently, it has been shown that chromophores with twisted π-electron systems in a cyclophane system having five-membered hetero-aromatic rings as electron donors and a bridging double bond as electron acceptor exhibit molecular hyperpolarizability with exceptionally high μβ values [18,127]. Interestingly, quantum-chemical calculations suggest that these cyclophane architectures with one or two unsaturated bridging double bonds reveal intramolecular charge transfer characteristics in the lowest excited state [18,127].…”
Section: Charge-transfer Interactions In Cyclophanesmentioning
confidence: 99%
“…More recently, it has been shown that chromophores with twisted π-electron systems in a cyclophane system having five-membered hetero-aromatic rings as electron donors and a bridging double bond as electron acceptor exhibit molecular hyperpolarizability with exceptionally high μβ values [18,127]. Interestingly, quantum-chemical calculations suggest that these cyclophane architectures with one or two unsaturated bridging double bonds reveal intramolecular charge transfer characteristics in the lowest excited state [18,127]. Accordingly, it is intriguing to study the nature of the excited states delocalization in detail for these bichromophoric cyclophanes with unsaturated tethers.…”
Section: Charge-transfer Interactions In Cyclophanesmentioning
confidence: 99%
See 1 more Smart Citation
“…Once the bromo compounds 14 a and 14 b are in hand, the next step is to prepare sulfur containing amino acid derivatives by reaction with potassium thioacetate and it was reacted with bromo compounds 14 a and 14 b in the presence of potassium carbonate in methanol to produce sulphide containing amino acid derivatives in an excellent yield (Scheme 3). [33] Since, S-allyl compounds show biologically activity, we expanded the substrate scope with a wide range of benzyl bromides (Scheme 3). The treatment of allyl and propargyl bromide with potassium thioacetate delivered the unsaturated AAA derivatives 31-34, (Figure 4) in 87-91% yields.…”
Section: Resultsmentioning
confidence: 99%
“…Presumably, the resonance contribution in 9 may desymmetrize the structure for 10, resulting in optical nonlinearity. 37 When R 1 is a sterically hindered tert-butyl group and R 2 is Me3Si in eq 20, reaction of the propargylic dithioacetal with BuLi followed by an aldehyde gives the carbinol 12, which is converted stereoselectively under Mitsunobu conditions into the corresponding enyne 13. 38 This transformation has been used for the iterative synthesis of Z-oligodiacetylenes 14.…”
Section: Annulation Of Propargylic Dithioacetals Leading To Furans Or...mentioning
confidence: 99%